2006
DOI: 10.1111/j.1747-0765.2006.079_6.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf color diagnosis and nitrogen management for winter wheat “Kitanokaori” in Hokkaido

Abstract: (Jpn. J. Soil Sci.Plant Nutr., 77, 293–298, 2006) “Kitanokaori” is a new variety of wheat for bread use bred at the National Agricultural Research Center for Hokkaido Region. The grain protein content of wheat for bread use should be higher than 120 g kg−1. Much nitrogen application is necessary to obtain high grain protein content. Therefore, it is necessary to determine the optimum amount of nitrogen to obtain the required protein content and to prevent nitrogen from remaining in the soil. The nutrition diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
8
2
Order By: Relevance
“…1). Many scientists have reported a signifi cant interaction between protein content of grain at maturity and the leaf blade SPAD value before heading or at anthesis in wheat (Matsunaka et al, 1997;Sato, 2000;Fukushima et al, 2004;López-Bellido et al, 2004;Spaner et al, 2005;Takebe et al, 2006;Poblaciones et al, 2009). In the present study, we confi rmed this result, but found that the protein content of grain had a higher positive correlation with leaf blade DW and the LAI ×SPAD value than with the SPAD value ( Table 6).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1). Many scientists have reported a signifi cant interaction between protein content of grain at maturity and the leaf blade SPAD value before heading or at anthesis in wheat (Matsunaka et al, 1997;Sato, 2000;Fukushima et al, 2004;López-Bellido et al, 2004;Spaner et al, 2005;Takebe et al, 2006;Poblaciones et al, 2009). In the present study, we confi rmed this result, but found that the protein content of grain had a higher positive correlation with leaf blade DW and the LAI ×SPAD value than with the SPAD value ( Table 6).…”
Section: Discussionsupporting
confidence: 77%
“…In rice, there was a positive correlation between leaf color value and N contents of leaf and stem (Tanno et al, 1982;Kumagai et al, 1991). In wheat, there was a similar positive correlation between leaf color value and N contents of whole-plant and leaf (Matsunaka et al, 1997;Sato, 2000;Takebe et al, 2006). The leaf blade SPAD value is closely related to the chlorophyll content of leaf (Yadava, 1986;Campbell et al, 1990;Schaper and Chacko, 1991).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…"Chihokukomugi"). Takebe et al (2006) also reported that leaf color measurement using a chlorophyll meter (SPAD502) at the full heading stage is a good index for deciding the amount of additional N fertilization required for the winter wheat cultivar "Kitanokaori". Both of these technologies shared the same purpose of adjusting the grain protein to within the level required for flour quality.…”
Section: Introductionmentioning
confidence: 99%
“…In fact farmers often apply an extra dose of N to avoid the risk of deficiency as it is linked with irrigation events. In many regions farmers are applying N fertilizer at levels that exceed the dose suggested by the government extension services (Takebe et al, 2006;Singh et al, 2011). The hand held Greenseeker (Trimble Navigation Limited, Sunnyvale, CA, USA) is an active optical crop canopy sensor with a red (650±10nm) and a NIR (770±15nm) is commercially available and used widely.…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%